Quorum sensing communication between bacteria and human cells: signals, targets, and functions - Holm, Angelika; Vikström, Elena (Frontiers in Plant Science, 2014)
Both direct and long-range interactions between pathogenic Pseudomonas aeruginosa bacteria and their eukaryotic hosts are important in the outcome of infections. For cell-to-cell communication, these bacteria employ the quorum sensing (QS) system to pass on information of the density of the bacterial population and collectively switch on virulence factor production, biofilm formation and resistance development. Thus, QS allows bacteria to behave as a community to perform tasks which would be impossible for individual cells, e.g. to overcome defense and immune systems and establish infections in higher organisms. This review highlights these aspects of QS and our own recent research on how P.aeruginosa communicates with human cells using the small QS signal molecules N-acyl homoserine lactones (AHL). We focus on how this conversation changes the behavior and function of neutrophils, macrophages and epithelial cells and on how the signaling machinery in human cells responsible for the recognition of AHL. Understanding the bacteria-host relationships at both cellular and molecular levels is essential for the identification of new targets and for the development of novel strategies to fight bacterial infections in the future.